Evaluation Of Murrah Buffalo Bulls Through Field Progeny Testing Programme In Amul Milk Shed Area - Patel, S.B.; Thesia, M.J.; M.G. , Butani (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Field Progeny Testing in Murrah buffalo bulls was initiated in the early 1988 by the Amul Research and Development Association (ARDA) under technical guidance and assistance of National Dairy Development Board, Anand (NDDB). The Murrah buffalo bull calves regularly purchased from breeding tract (Haryana and Punjab), born out of elite buffaloes and male calves of proven sires born through nominated mating were taken as candidate bulls. For baseline information, the milk production data of the registered buffaloes under Surti buffalo bulls Progeny Testing Programme of selected 35 villages of Kheda and Anand districts recorded on monthly intervals in the field along with other necessary reproduction data was utilized to compute the different traits of economic importance. Since the inception of the program, 186 bulls have been put under progeny testing program and 123 bulls were evaluated by daughter average method, out of which 74 buffalo bulls contributed positively in milk production of daughters with predicted difference of 60.04 kg in 305 days that ranged from 3.0 to 178.6 kg between bulls.